Allium discoloration: the nature of onion pinking and garlic greening - R. Kubec; M. Hrbáčová; R. A Musah; J. Velíšek (Czech Journal of Food Sciences, 2004)
Precursors involved in the formation of pink and green-blue pigments during onion and garlic processing, respectively, have been studied. It has been confirmed that the formation of both pigments is of a very similar nature, with (E)-S-(1-propenyl)cysteine sulfoxide (isoalliin) serving as the primary precursor. Upon disruption of the tissue, isoalliin and other S-alk(en)ylcysteine sulfoxides are enzymatically cleaved, yielding prop-1-enylcontaining thiosulfinates [CH3CH = CHS(O)SR; R = methyl, allyl, propyl, 1-propenyl], among others. The latter compounds subsequently react with amino acids to produce the pigments. Whereas the onion and leek-related propyl, prop-1-enyl and methyl derivatives can form pink, pink-red and magenta compounds, those containing the allyl group yield dark blue products after reacting with glycine at pH 5.0.